2021
DOI: 10.3389/fimmu.2021.673021
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid IL-17A Could Predict Acute Disease Severity in Non-NMDA-Receptor Autoimmune Encephalitis

Abstract: IntroductionMost of our knowledge into autoimmune encephalitis (AE) comes from N-Methyl-D-Aspartate Receptor (NMDAR) encephalitis. The concentrations of cytokines in cerebrospinal fluid (CSF) including IL-17A have been found to be increased and associated with poor outcome. However, data on the cytokine concentration in CSF and its correlation with outcome is lacking for other types of AE.ObjectiveTo report the concentrations of CSF sIL-2R, IL-6, IL-8, IL-10 and IL-17A and to correlate it with acute disease se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Thus, Chemokine (C-X-C motif) ligand 13 (CXCL-13) has been reported as a potential biomarker of treatment response and relapse rate in a bigger cohort of NMDAR-AE patients, but long-term outcomes in relation to CXCL-13 remains to be further elucidated ( 14 ). Similarly, cytokine studies, mostly in NMDAR-AE patients, have suggested particularly Interleukin-17A as a biomarker of disease severity at onset and a poor prognosis ( 15 18 ). Limited studies have investigated neuronal surface autoantibody titers as diagnostic or prognostic biomarkers and high titers may indicate poor prognosis and malignancy ( 4 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Chemokine (C-X-C motif) ligand 13 (CXCL-13) has been reported as a potential biomarker of treatment response and relapse rate in a bigger cohort of NMDAR-AE patients, but long-term outcomes in relation to CXCL-13 remains to be further elucidated ( 14 ). Similarly, cytokine studies, mostly in NMDAR-AE patients, have suggested particularly Interleukin-17A as a biomarker of disease severity at onset and a poor prognosis ( 15 18 ). Limited studies have investigated neuronal surface autoantibody titers as diagnostic or prognostic biomarkers and high titers may indicate poor prognosis and malignancy ( 4 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In concordance with the scarce inflammatory reaction distinctive of anti-LGI1 encephalitis, only a few studies found significant differences in intrathecal cytokine levels compared to controls. 55 , 56 High CSF levels of CXCL-13 were observed despite an unremarkable CSF analysis, highlighting that a humoral CNS immune response may be present even in the absence of an evident inflammatory CSF. However, serum levels were generally higher, indicating a peripheral synthesis and a subsequent leakage into the CNS.…”
Section: Methodsmentioning
confidence: 97%
“…The findings suggested that CSF IL-17A could be useful in determining the severity of AE at the outset. Consequently, CSF IL-17A could be a promising therapeutic target and an effective tool for evaluating early immunosuppressive therapy [ 24 ].…”
Section: Reviewmentioning
confidence: 99%